Enhancing EFL Students’ Reading Comprehension through the Use of Schema Activation Techniques - Samudera, Elang Garda; Lolita, Yuri (Universitas PGRI Adi Buana Surabaya, 2025)
This study investigates the effect of the Schema Activation Strategy on EFL students’ reading comprehension, particularly in analyzing and interpreting narrative texts. A quasi-experimental design was employed involving 68 eleventh-grade students divided into an experimental group and a control group. Over four weeks, the experimental group received instruction using schema-based activities such as K-W-L charts, pre-teaching vocabulary, visual aids, and case-based reading, while the control group was taught using conventional methods. Pre-tests and post-tests were administered to both groups, and the data were analyzed using descriptive statistics and inferential analysis (paired and independent samples t-tests). The results showed that both groups improved their reading comprehension performance; however, the experimental group demonstrated a significantly higher mean gain (9.94 points) compared to the control group (8.83 points). Furthermore, an independent t-test revealed a statistically significant difference in post-test scores between the groups (t = 2.439, p = 0.017), favoring the experimental group. These findings confirm that schema activation strategies, which engage learners' prior knowledge, effectively enhance inferential understanding, critical thinking, and textual interpretation in EFL contexts. The study suggests incorporating schema-based reading instruction into the EFL curriculum to foster deeper comprehension and metacognitive skills.